Exploring Reasons of Formula 1 Team’s Underperforming in F1 Racing - Song, Borui (Transactions on Economics, Business and Management Research, 2024)
The COVID-19 pandemic imposed unprecedented challenges on Formula 1 (F1), intensifying financial and technological disparities among teams. Haas F1, a relatively new entrant to the sport, has struggled with consistent underperformance since its peak in 2018. This paper explores the factors contributing to Haas F1’s decline, focusing on financial limitations, reliance on external technology, and ineffective global operations. The 2020 pandemic exacerbated the team’s existing struggles, particularly in securing sponsorship and navigating the new budget cap regulations introduced in 2021. Additionally, Haas’s dependence on Ferrari for essential car components has constrained its technological innovation, leading to further competitive disadvantages. Despite attempts to restructure the team and improve performance through financial and strategic changes, Haas has yet to achieve sustained success. This paper examines Haas F1’s case through qualitative analysis and proposes improvements, including diversified funding strategies and increased investment in internal research and development, to enhance competitiveness in the evolving F1 landscape.